Structural quality of healthcare facilities in India. Issue 6 (9th July 2018) - Armenta, Bianca; Rathi, Naveen; Assasnik, Nushean; Kamimura, Akiko
Abstract : Purpose: Although India has a number of health issues, the healthcare facilities in India are insufficient due to poor quality of care. The purpose of this paper is to examine the factors affecting the structural quality of healthcare facilities in India. Design/methodology/approach: This study used the medical facility data from the India Human Development Survey-II, 2011–2012 (ICPSR 36151) ( n =4, 218). Logistic regression was conducted to predict structural quality of healthcare facilities. Findings: The results suggest that it is difficult to have all standard resources available at health care facilities in India. Surprisingly, having a drinking water source inside the health facility appears to be an indicator of poor structural quality of health care facilities. Having a water source inside a health care facility is associated with not having a separate exam room and not having a sink to wash hands. A higher registration fee was associated with good structural quality and with having a separate exam room and having a sink to wash hands. Originality/value: This study shows the complexity of providing quality health care to the poor, particularly in developing countries. Research on quality of healthcare facilities in India is needed to improve the health of the population. Little research has been done on the factors influencing the structural quality of the healthcare facilities in India. This study is an important contribution to the current knowledge of structural healthcare facility standards and its influences in India.